The Utility of Both Hard and Soft Power in Modern International Relations - Davit Tchotchua (International Journal of Economic Integration and Regional Competitiveness, 2024)
This essay's first section defines hard and soft power and how they work together to create soft power. Next, various instances of the two principles' application in the formulation of foreign policy are discussed in order to evaluate their efficacy. There are also instances of the application of smart power in this discussion. According to the article, soft power's durability and longevity make it a more effective and efficient notion in modern global politics. Hard power, however, is becoming less valuable as the world order shifts against it. In the modern international system, smart power tactics are just as significant as soft power tactics. Nye proposed the concept of hard power and soft power distinctions almost twenty years ago. He characterizes command or hard power as coercive power used through inducements or threats, and power as the "ability to affect others to get the outcomes one wants" in general. Hard power depends on concrete power resources like armed troops or financial resources and is based on economic sanctions , forceful diplomacy, and military action. Hard power examples include the German invasion of Poland in 1939 and the UN economic sanctions imposed on Iraq in 1991 after the first Gulf War. Because of all of the above, it is important to analyze the types of power and their effectiveness, what is the impact of soft and hard power in modern international relations, both separately and in tandem.